A Study on the Implementation of Flipped Classrooms in Chinese Higher Education: Perceptions, Benefits, and Challenges (Journal of Interdisciplinary Insights, 2024)
This study investigates the implementation of flipped classrooms in Chinese higher education, focusing on the perceptions, benefits, and challenges experienced by both faculty and students at Hebei XX University. Utilizing a qualitative research approach, semi-structured interviews were conducted with 25 faculty members and 25 students who have participated in flipped classroom settings. The findings reveal that the flipped classroom model significantly enhances student engagement, critical thinking, and problem-solving skills while providing increased flexibility and personalized learning opportunities. However, the study also identifies substantial challenges, including faculty resistance, technological barriers, and issues related to student adaptation and time management. The results align with existing literature on flipped classrooms, underscoring the need for robust institutional support and professional development to facilitate successful implementation. The study's implications suggest that with adequate support, flipped classrooms can effectively transform traditional educational environments in Chinese higher education, promoting active and student-centered learning.